Hospital Pharmacy Inventory Management: Importance and Efficiency Strategies (CIPEEX, 2025)
Introduction: Inventory management in hospital pharmacies is essential to ensure the availability, quality, and safety of medications, as well as to avoid waste and reduce costs. The complexity of the hospital environment requires efficient methods of procurement, storage, and distribution, ensuring the rational use of resources. Objective: To analyze the importance of inventory management in hospital pharmacies and to identify tools that contribute to greater efficiency in medication management. Methodology: This is a narrative review based on articles, technical manuals, and case studies on hospital management. Documents published in Portuguese between 2010 and 2024, available in academic databases and institutional publications, were considered. Results: The studies demonstrated that the use of tools such as the ABC curve, drug standardization, and computerized control systems favors purchase planning, reduces financial losses, and increases patient safety. The role of the pharmacist is essential in this process, as it involves continuous monitoring, defining minimum and maximum stock levels, and integration with administrative teams. Conclusion: Inventory management in hospital pharmacies is configured as a strategic activity that integrates clinical, administrative, and financial aspects. Its efficient execution directly contributes to the institution’s sustainability, patient safety, and the quality of care provided.
Keywords: Hospital pharmacy; Inventory management; Health logistics